In vitro and in vivo biological performance of porous Ti alloys prepared by powder metallurgy - Prado, Renata Falchete do [UNESP]; Esteves, Gabriela Campos [UNESP]; De Souza Santos, Evelyn Luzia [UNESP]; Griti Bueno, Daiane Acacia [UNESP]; Alves Cairo, Carlos Alberto; Oliveira De Vasconcellos, Luis Gustavo [UNESP]; Sagnori, Renata Silveira; Pereira Tessarin, Fernanda Bastos [UNESP]; Oliveira, Felipe Eduardo [UNESP]; De Oliveira, Luciane Dias [UNESP]; Lima Villaca-Carvalho, Maria Fernanda [UNESP]; Rodrigues Henriques, Vinicius Andre; et al. (Public Library Science, 2018)
Titanium (Ti) and Ti-6 Aiuminium-4 Vanadium alloys are the most common materials in implants composition but beta type alloys are promising biomaterials because they present better mechanical properties. Besides the composition of biomaterial, many factors influence the performance of the biomaterial. For example, porous surface may modify the functional cellular response and accelerate osseointegration. This paper presents in vitro and in vivo evaluations of powder metallurgy-processed porous samples composed by different titanium alloys and pure Ti, aiming to show their potential for biomedical applications. The porous surfaces samples were produced with different designs to in vitro and in vivo tests. Samples were characterized with scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS) and elastic modulus analyses. Osteogenic cells from newborn rat calvaria were plated on discs of different materials: G1-commercially pure Ti group (CpTi); G2-Ti-6AI-4V alloy; G3-Ti-13 Niobium-13 Zirconium alloy; G4-Ti-35 Niobium alloy; G5-Ti-35 Niobium-7 Zirconium-5 Tantalum alloy. Cell adhesion and viability, total protein content, alkaline phosphatase activity, mineralization nodules and gene expression (alkaline phosphatase, Runx-2, osteocalcin and osteopontin) were assessed. After 2 and 4 weeks of implantation in rabbit tibia, bone ingrowth was analyzed using micro-computed tomography (mu CT). EDS analysis confirmed the material production of each group. Metallographic and SEM analysis revealed interconnected pores, with mean pore size of 99,5 mu m and mean porosity of 42%, without significant difference among the groups (p > 0.05). The elastic modulus values did not exhibit difference among the groups (p > 0.05). Experimental alloys demonstrated better results than CpTi and Ti-6AI-4V, in gene expression and cytokines analysis, especially in early experimental periods. In conclusion, our data suggests that the experimental alloys can be used for biomedical application since they contributed to excellent cellular behavior and osseointegration besides presenting lower elastic modulus.